Implementation of the Policy for the Utilization of the Allocation of Rerer Village Funds in Kombi District Minahasa Regency - Rarumangkay, Jeanne Dianne; Lumingkewas, Lexi; Tumbel, Goinpeace (Technium Social Sciences Journal, 2021)
This study aims to analyze the Utilization of Rerer Village Fund Allocation, Kombi District, Minahasa Regency. This research uses a qualitative approach to investigate the phenomenon of policy implementation using ADD Rerer, Kombi District, Minahas Regency. Sources of interview data are 3 Community Leaders, 3 Head of Guard, 3 Village Apparatus, 3 BPD, Old Law. The results of the study concluded that: a). The socialization that impacts the understanding of Village Apparatus, BPD, PKK and community members has not been carried out effectively and efficiently, b). communication has not been created between the Village Apparatus, BPD, PKK and community members, c). It has not yet formed the implementor’s attitude, commitment, or disposition to support policy implementation, d). The social condition of the community has not yet been created to participate in policy implementation. For this reason, it is recommended that: a). conduct socialization that impacts understanding the Village Apparatus, BPD, PKK and community members effectively and efficiently, b). Intensive communication between Village Apparatus, BPD, PKK and community members in implementing policies, c). Required commitment or disposition from the implementer to implement the policy, d). To prepare the social conditions of the community so that participation in policy implementation is minimized, it is recommended that The Minahasa Regency Government issued a new policy in this regard.